Creating the Russian Peril: Education, the Public Sphere, and National Identity in Imperial Germany, 1890-1914 - Paddock, Troy R. E. (Camden House, 2010)
German attitudes toward and stereotypes of Russia before the First World War and how they were inculcated in the public.
Keywords: 1871-1918; 19th century; Education; 19th century; Nationalism; 20th century; Germany; 20th century; Nationalism; Foreign public opinion, German; Russia; Germany; Germany; Germany; Germany; Russia; History; History; Education; Political aspects; Press coverage; Public opinion; Relations; Russia; Russia; SCSU Faculty Scholar Award; award_winner; dept.his; faculty_collection